ANÁLISIS COMPARATIVO DE LOS HORIZONTES EPISTEMOLÓGICOS DEL REDISEÑO 2012 Y EL REDISEÑO CURRICULAR 2015 DE LA CARRERA DE BIOLOGÍA QUÍMICA Y LABORATORIO/ PEDAGOGÍA DE LA QUÍMICA Y BIOLOGÍA. - Caichug Rivera, Daniela Margoth (2020)
This research project aimed to compare the epistemological horizons of the redesigns of the careers of Biology, Chemistry and Laboratory / Pedagogy of Chemistry and Biology, the study aims to answer the problem: How the analysis and comparison of the epistemological horizons of redesign of the career of Chemical and Laboratory Biology (2012) and the pedagogy of Chemistry and Biology (2015) contribute to the professional training of career students, by studying the nature and epistemological relevance and its influence on curricular meshes and learning outcomes. For its understanding, an instrument (signing) was developed, which allows us to identify the epistemological horizons using documentary analysis together with the deductive method, using primary sources the curricular redesigns. In the 2012 redesign 44% and in 2015 3.33% of learning outcomes do not apply to an epistemological school which results in a problem since epistemology makes a science become the object of knowledge. At the end of the investigation it was concluded that both redesigns are framed in the learning of biology, chemistry, education sciences and ICT. The 2012 redesign offers technical knowledge of natural sciences, management processes and resource development, educational materials. The 2015 design offers a strength in interdisciplinarity, where curricular integration arises, the integrative chairs that articulate subjects with knowledge and the constructs that differentiate the different approaches, theories or models to acquire a broader view of the context.